Numerical vorticity quantification in the Kvichak River, Alaska (USA). (June 2016) - Diedrich, Timothy J; Toniolo, Horacio
Hydrokinetic turbine deployment locations have historically been sited based on the power density and theoretical hydraulic power. Neither of these parameters account for the turbulence within the fluid column. It is the goal of this paper to quantify the vorticity magnitude, based on previously collected Acoustic Doppler Current Profiler data, associated with transects of the Kvichak River near Igiugig, Alaska (USA). The Kvichak River is a proposed site for the deployment of a hydrokinetic turbine, where three siting recommendations have previously been made by others. Vorticity magnitude results are plotted in cross-sectional, two-dimensional contour format and are utilized to further the analysis and recommendations of the deployment site along the study area. A vector system rotation is applied to correlate Acoustic Doppler Current Profiler data output to a regional coordinate system. Results indicate that higher levels of vorticity magnitude are associated with two of the primary recommended turbine deployment sites and provide confidence in the suitability of the sole remaining proposed turbine deployment location.